2011
DOI: 10.1021/es201641x
|View full text |Cite
|
Sign up to set email alerts
|

Laser Ablation ICP-MS Co-Localization of Mercury and Immune Response in Fish

Abstract: Mercury (Hg) contamination is a global issue with implications for both ecosystem and human health. In this study, we use a new approach to link Hg exposure to health effects in spotted gar (Lepisosteus oculatus) from Caddo Lake (TX/LA). Previous field studies have reported elevated incidences of macrophage centers in liver, kidney, and spleen of fish with high concentrations of Hg. Macrophage centers are aggregates of specialized white blood cells that form as an immune response to tissue damage, and are cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 45 publications
5
34
1
Order By: Relevance
“…Recently, Hg and MAs were shown to be colocalized in wild fish liver tissue, directly linking Hg to cellular damage [24]. Analyses using LA ICP-MS of perch from the present study support these findings.…”
Section: Macrophage Aggregatessupporting
confidence: 86%
See 3 more Smart Citations
“…Recently, Hg and MAs were shown to be colocalized in wild fish liver tissue, directly linking Hg to cellular damage [24]. Analyses using LA ICP-MS of perch from the present study support these findings.…”
Section: Macrophage Aggregatessupporting
confidence: 86%
“…Analyses using LA ICP-MS of perch from the present study support these findings. Although Hg accumulation in perch MAs was generally lower than that observed in spotted gar by Barst et al [24], 94% of perch MAs contained higher Hg isotope counts than adjacent hepatocytes. This Hg accumulation within liver MAs, in addition to the positive relationships between the prevalence of liver MAs and tissue Hg concentrations, strengthens our hypothesis that Hg exposure results in an increased occurrence of MAs in these perch.…”
Section: Macrophage Aggregatescontrasting
confidence: 60%
See 2 more Smart Citations
“…Batchelar et al (2013) concluded that the enhanced presence of MAs in tissues of yellow perch from KNPNHS is suggestive of a negative impact of Hg at the cellular level. The positive relationship between the frequency of MAs and tissue Hg concentrations has also been reported for other wild fish species (Barst et al 2011;Meinelt et al 1997;Schwindt et al 2008). Furthermore, laser ablation and inductively coupled plasma mass spectrometry showed that Hg and MAs were co-localized in hepatic tissue and that Hg accumulated in higher amounts in MAs than in the surrounding liver parenchyma (Barst et al 2011;Batchelar et al 2013).…”
Section: Introductionsupporting
confidence: 65%